2009
DOI: 10.1099/ijs.0.001651-0
|View full text |Cite
|
Sign up to set email alerts
|

Kiloniella laminariae gen. nov., sp. nov., an alphaproteobacterium from the marine macroalga Laminaria saccharina

Abstract: A novel alphaproteobacterium, strain LD81 T , was isolated from the marine macroalga Laminaria saccharina. The bacterium is mesophilic and shows a typical marine growth response. It is a chemoheterotrophic aerobe with the potential for denitrification. Growth optima are 25 6C, pH 5.5 and 3 % NaCl. Strain LD81 T has a unique phylogenetic position, not fitting any of the known families of the Alphaproteobacteria. The 16S rRNA gene sequence revealed a distant relationship to species of several orders of the Alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…Considering all available evidence, including our own observations (Staufenberger et al 2008, Lachnit et al 2009, Wiese et al 2009a, it is reasonable to conclude that a highly specific association of bacterial communities with marine macroalgae exists. It has been proposed that the physiological and biochemical properties of macroalgae predetermine the composition of the adhering microbial communities (Beleneva & Zhukova 2006).…”
Section: Bacterial Communities Associated With Macroalgaementioning
confidence: 64%
“…Considering all available evidence, including our own observations (Staufenberger et al 2008, Lachnit et al 2009, Wiese et al 2009a, it is reasonable to conclude that a highly specific association of bacterial communities with marine macroalgae exists. It has been proposed that the physiological and biochemical properties of macroalgae predetermine the composition of the adhering microbial communities (Beleneva & Zhukova 2006).…”
Section: Bacterial Communities Associated With Macroalgaementioning
confidence: 64%
“…The 16S rDNA sequence determined for the Kiloniella sp. was 96% identical to that of Kiloniella laminariae LD81 T , the only cultured Kiloniellaceae member and an aerobic chemoheterotrophic spirillum isolated from the marine brown alga Laminaria saccharina in the Baltic sea (Wiese et al 2009). It was also 99% identical to 'Kopriimonas byanusanensis', a novel species not described formally, and from this high sequence similarity we propose the name 'Candidatus Kopriimonas aquarianus' for this newly identified Kiloniella relative.…”
Section: Discussionmentioning
confidence: 91%
“…Colwelliaceae include marine aerobic and facultative anaerobic marine members that reduce nitrate to nitrite (Ivanova et al, 2004) and have been shown to inhabit industrial saline wastewater (Yoshie et al, 2004; Yoshie et al, 2006) and marine RAS denitrification systems (Interdonato, 2012; Martins et al, 2013). Thalassospira include members possessing aerobic or facultative anaerobic metabolism that use nitrate as electron acceptor (Wiese et al, 2009) and have been identified in denitrification bioreactor for saline water with poly butylene succinate as carbon source (Luo et al, 2013) and in the Mediterranean Sea (Hütz et al, 2011; Cortés-Lara et al, 2015). Finally, in addition to bacteria involved in nitrogen cycling, bacteria capable of sulfur metabolism were identified in the DBRs, including a representative of the genus Arcobacter , which oxidizes sulfide to sulfur (Vandamme et al, 2005).…”
Section: Discussionmentioning
confidence: 99%